Ulinastatin attenuates isoflurane-induced cognitive dysfunction in aged rats by inhibiting neuroinflammation and β-amyloid peptide expression in the brain. (3rd October 2019) - Guo, Mingyan; Zhu, Xiaoqiu; Xu, Hui; Li, Jin; Yang, Shangze; Zuo, Zhiyi; Lin, Daowei
ABSTRACT: Objective : Postoperative neurocognitive disease (PNCD) in the aged is a major clinical problem with unclear mechanisms. This study was designed to explore the mechanisms for ulinastatin (UTI) to attenuate isoflurane-induced cognitive decline in Fischer-344 rats. Methods : The rats were divided into four groups: Control (0.9% saline only), Isoflurane (exposure to 1.2% isoflurane), Isoflurane-plus-UTI (exposure to 1.2% isoflurane followed by 100, 000 U/kg UTI injection i.v .) and UTI-plus-isoflurane (i.v. of 100, 000 U/kg UTI followed by 1.2% isoflurane exposure). After respective tests, the concentrations of tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in the brain were determined by ELISA the expression of β-amyloid peptide (Aβ) and cleaved caspase-3 were measured by Western blot. Ratio of apoptotic cells after Barnes maze challenge was assessed by TUNEL assay. Results : In both Barnes Maze training and challenge, results indicated isoflurane-impaired learning capacity, while pre-and post-treatment with UTI could attenuate this phenomenon. The ratio of apoptotic cells and the expression of cleaved caspase-3 were increased after isoflurane exposure, indicating that isoflurane could induce neuronal apoptosis, while both pre- and post-treatment with UTI could diminish these effects. Moreover, UTI inhibited the expression of TNF-α, IL-1β and Aβ induced by isoflurane in rat brain harvested at 16 h after isoflurane exposure. Conclusion : These results suggest that UTI inhibits neuronal apoptosis in rat brain by attenuating increased expression of Aβ42 and inflammatory cytokines, which may contribute to its alleviation of isoflurane-induced cognitive dysfunction in rats. Moreover, UTI pre-treatment before isoflurane exposure showed more effective than post-treatment.